2017
DOI: 10.1002/adem.201700572
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Poly(acrylonitrile) Electrospun Nanofiber Membranes for Airborne Nanomaterials Filtration

Abstract: The potential of poly(acrylonitrile) electrospun membranes with tuneable pore size and fiber distributions were investigated for airborne fine-particle filtration for the first time. The impact of solution concentration on final membrane properties are evaluated for the purpose of designing separation materials with higher separation efficiency. The properties of fibers and membranes are investigated systematically: the average pore distribution, as characterized by capillary flow porometry, and thermo-mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Comparing these studies, it is possible to note that the filters reported in this study are composed of PAN material of small fibers diameter that probably explains the high-quality factor. In addition, a very high filtration efficiency (approximately 100% filtration efficiency) in the range of 9 to 300 nm aerosol particles diameters and quality factor (0.05) were reached by our PAN/Ag NPs filter in comparison to commercial filters (filtration efficiency less than 80% and quality factor of 0.02) reported elsewhere [17], [70], [71]. It should be noted that the face velocity, particle size, and material composition may be different in the aforementioned studies.…”
Section: Filtration Performance Of Nanofiber Filtersmentioning
confidence: 53%
“…Comparing these studies, it is possible to note that the filters reported in this study are composed of PAN material of small fibers diameter that probably explains the high-quality factor. In addition, a very high filtration efficiency (approximately 100% filtration efficiency) in the range of 9 to 300 nm aerosol particles diameters and quality factor (0.05) were reached by our PAN/Ag NPs filter in comparison to commercial filters (filtration efficiency less than 80% and quality factor of 0.02) reported elsewhere [17], [70], [71]. It should be noted that the face velocity, particle size, and material composition may be different in the aforementioned studies.…”
Section: Filtration Performance Of Nanofiber Filtersmentioning
confidence: 53%
“…Electrospun nanofiber membranes possess many advantages such as interconnected open pores, small pore size, high porosity and large surface-to-volume ratio, which make them promising candidates for air filtration. Al-Attabi [10], Wang [11] and Zhang [12] found that nanofiber membranes have superior FE owing to the nano-scale fiber diameter and small pore size, but they also exhibit high airflow resistance due to the compact structure [13].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the capture efficiency of fine particles has attracted more attention because of the negative impact of fine particles on human health [1][2][3]. In particular, highefficiency particulate air (HEPA) filters need to be designed to effectively capture ultrafine particles smaller than 300 nm [4,5], which is important to produce clean breathable air and also to ensure safety in biosafety laboratories and the nuclear industry [6][7][8].…”
Section: Introductionmentioning
confidence: 99%